2004
DOI: 10.1111/j.1365-2893.2004.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in Greek patients with chronic hepatitis C and in patients with diverse nonviral hepatic diseases*

Abstract: Occult hepatitis B virus (HBV) infection has been reported in patients with chronic hepatitis C who are negative for HBV surface antigen (HBsAg). However, the significance of 'silent' HBV in hepatitis C virus (HCV) infection is unknown. We investigated 540 subjects for the presence of occult HBV in Greek HCV patients, patients with nonviral liver diseases and healthy donors in an attempt to determine the frequency and importance of this phenomenon. One hundred and eighty-seven anti-HCV(+)/HBsAg(-) patients' se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 52 publications
8
35
1
1
Order By: Relevance
“…The obtained results were confirmed by other studies as well (1,9,11,(20)(21)(22)(23)(24). The number of studies that have established an association between the presence of occult HBV infection and the genotype of HCV virus is small (25,26), serum level of HCV RNA (9,13,15) or transaminase activity (25,27).…”
Section: Discussionsupporting
confidence: 77%
“…The obtained results were confirmed by other studies as well (1,9,11,(20)(21)(22)(23)(24). The number of studies that have established an association between the presence of occult HBV infection and the genotype of HCV virus is small (25,26), serum level of HCV RNA (9,13,15) or transaminase activity (25,27).…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, HBV DNA has been found in serum by PCR in 6.7% to 52% (13,15,16) of HBsAg-negative patients with chronic HCV infection, in 5% to 76% (7,10,30) of patients with chronic liver disease of no defi ned etiology, and in 0% (15) to 15% (21) of healthy donors.…”
Section: Discussionmentioning
confidence: 95%
“…Despite evidence that co-infection may accelerate the progress to liver disease (9,41) , be related to the emergence of HCC (34,37,38) , and adversely infl uence the response to HCV treatment (7,9,13,41) , other studies show that occult infection does not interfere with the natural history of the disorder in this population (12,15,16,22) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of occult HBV infection in chronic hepatitis C virus (HCV) infection is perhaps the most extensively studied. Cacciola et al (29) not only found higher rates of occult HBV infection among patients with HCV-related chronic liver disease but also found liver cirrhosis more frequently among chronic HCV patients with (76,91,128,133,191,241). Occult HBV infection has been associated with liver enzyme flares during chronic HCV infection (235) without changes in HCV RNA levels (127).…”
Section: Clinical Relevancementioning
confidence: 99%